Rapid pacing and high‐frequency jet ventilation additively improve catheter stability during atrial fibrillation ablation. (27th April 2020) - Aizer, Anthony; Qiu, Jessica K.; Cheng, Austin V.; Wu, Patrick B.; Barbhaiya, Chirag R.; Jankelson, Lior; Linton, Patrick; Bernstein, Scott A.; Park, David S.; Holmes, Douglas S.; Chinitz, Larry A.
Abstract: Introduction: Catheter stability during atrial fibrillation ablation is associated with higher ablation success rates. Rapid cardiac pacing and high‐frequency jet ventilation (HFJV) independently improve catheter stability. Simultaneous modulation of cardiac and respiratory motion has not been previously studied. The objective of this study was to determine the effect of simultaneous heart rate and respiratory rate modulation on catheter stability. Methods: Forty patients undergoing paroxysmal atrial fibrillation ablation received ablation lesions at 15 prespecified locations (12 left atria, 3 right atria). Patients were randomly assigned to undergo rapid atrial pacing for either the first or the second half of each lesion. Within each group, half of the patients received HFJV and the other half standard ventilation. Contact force and ablation data for all lesions were compared among the study groups. Standard deviation of contact force was the primary endpoint defined to examine contact force variability. Results: Lesions with no pacing and standard ventilation had the greatest contact force standard deviation (5.86 ± 3.08 g), compared to lesions with pacing and standard ventilation (5.45 ± 3.28 g; P < .01) or to lesions with no pacing and HFJV (4.92 ± 3.00 g; P < .01). Lesions with both pacing and HFJV had the greatest reduction in contact force standard deviation (4.35 ± 2.81 g; P < .01), confirming an additive benefit of each maneuver. Pacing and HFJV together was also associated with a reduction in the proportion of lesions with excessive maximum contact force ( P < .001). Discussion: Rapid pacing and HFJV additively improve catheter stability. Simultaneous pacing with HFJV further improves catheter stability over pacing or HFJV alone to optimize ablation lesions.